Trends in Accidents Involving Healthcare Workers in the Pre-Pandemic and Pandemic Periods: Injury Notifications from an Emergency Department - Claudia Cipollone; Paola Guerriero; Mario Muselli; Riccardo Mastrantonio; Giada Mastrangeli; Stefano Filauri; Leila Fabiani (Safety, 2024)
Occupational accidents are a serious public health issue. In this retrospective observational study, we examined all injuries involving healthcare workers of the Abruzzo Local Health Authority No. 1 (Italy) during the three years 2019–2021. Data were collected by tracing the injury reports filed by the emergency service during the workers’ admission and analyzing the cause, type, distribution by sex, and geographical district to which they belonged, taking into account the period before and during the COVID-19 pandemic outbreak. Most injuries (45.7%) were reported in the Marsica area; the most common cause was commuting accidents (10.7%). Assaults were more common among men (8.6%), while commuting accidents were more common among women (11.8%). In 36% of cases, the upper limbs were affected. The most common type of injury was contusions (22.2%). When the frequency of reports was compared between the pre-pandemic and pandemic periods, there was an increase in injuries in healthcare assistants (p = 0.052), while the percentage of injuries in administrative (p = 0.056) and other categories decreased (p = 0.002). This analysis allows us to identify points of interest relating to the Marsica area, to specific types of accidents, such as aggression and commuting accidents, and to specific duties.